Organic-inorganic hybrid sol-gelcoatings for metal corrosion protection: a review of recent progress - Figueira, R. B. (2015)
This paper is a review of the most recent and relevant achievements (from 2001 to 2013) on the development of organic–inorganic hybrid (OIH) coatings produced by sol–gel-derivedmethods to improve resistance to oxidation/corrosion of different metallic substrates and their alloys. This review is focused on the research of OIH coatings based on siloxanes using the sol–gel process conducted at an academic level and aims to summarize the materials developed and identify perspectives for further research. The fundamentals of sol–gel are described, including OIH classification, the interaction with the substrate, their advantages, and limitations. The main precursors used in the synthesis ofOIHsol–gel coatings for corrosion protection are also discussed, according to the metallic substrate used. Finally, a multilayer system to improve the resistance to corrosion is proposed, based on OIH coatings produced by the sol–gel process, and the future research challenges are debated.